2022
DOI: 10.1007/s10549-022-06644-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of secondary malignancy after radiotherapy for breast cancer: long-term follow-up of Japanese patients with breast cancer

Abstract: Purpose There have been very few reports of secondary malignancies after breast cancer treatment in Asia, particularly in Japan. This study aimed to evaluate the risk of secondary malignancies after radiotherapy (RT) in Japanese breast cancer patients. Methods This single-center retrospective study included patients who underwent RT between July 1961 and September 2006 for postoperative breast cancer. A total of 702 patients with a follow-up period of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is important to note that exposure to high and low doses of radiation 11 , can increase the risk of damage to the heart 4 and lungs 12 . Moreover the risk of second cancer induction on contralateral breast in particular for young woman must be considered like it is reported in literature 13 . Although less severe, the consequences and doses delivered to healthy mammary glands merit particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that exposure to high and low doses of radiation 11 , can increase the risk of damage to the heart 4 and lungs 12 . Moreover the risk of second cancer induction on contralateral breast in particular for young woman must be considered like it is reported in literature 13 . Although less severe, the consequences and doses delivered to healthy mammary glands merit particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that various types of SPCs occurred after breast cancer treatment with radiation (Li et al , 2021; Xia et al , 2022; Kim et al , 2023). Therefore, SPCs were regarded as one of the RT-associated long-term side effects (Mendes et al , 2017; Xie et al ., 2019; Okonogi et al ., 2022). Though controversies still existed, some previous studies had observed independent associations of RT and SPCs in several tumor types, such as breast, esophageal and lung (Duane et al ., 2021; Zareie et al , 2022; van Barele et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%